Software for Ranking Indian Scientists based on Citations to their Publications - Saxena, S.C.; Relan, Sonia; Murthy, S.S. (DESIDOC Journal of Library & Information Technology, 2003)
The paper describes the software developed at DESIDOC for ranking Indian scientists and technologists based on the citations to their publications as covered in Science Caution index (SCI). The software projides facilities for generating reports on highly cited authors, highly cited journals, highly productive institutions, weightage of authorship etc. quickly. This measure could be one of the important parameters ‘for rating the performance' of scientists for giving awards, promotions or other career incentives and for making appointments to important positions. http://dx.doi.org/10.14429/dbit.19.6.3502